2022
DOI: 10.3389/fpls.2022.942448
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the potential distribution of four endangered holoparasites and their primary hosts in China under climate change

Abstract: Climate change affects parasitic plants and their hosts on distributions. However, little is known about how parasites and their hosts shift in distribution, and niche overlap in response to global change remains unclear to date. Here, the potential distribution and habitat suitability of four endangered holoparasites and their primary hosts in northern China were predicted using MaxEnt based on occurrence records and bioclimatic variables. The results indicated that (1) Temperature annual range (Bio7) and Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 64 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, models of future distribution of H. ammodendron in Northwest China presented by Hong et al 91 indicated slight expansion of the potential range of this species. As summarized by Lu et al 29 , climate factors and niche overlaps between them can jointly affect the suitable habitats of parasitic plants and this is certainly true also for P. tournefortii.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, models of future distribution of H. ammodendron in Northwest China presented by Hong et al 91 indicated slight expansion of the potential range of this species. As summarized by Lu et al 29 , climate factors and niche overlaps between them can jointly affect the suitable habitats of parasitic plants and this is certainly true also for P. tournefortii.…”
Section: Discussionmentioning
confidence: 94%
“…hosts, competition, mimicry, herbivory) influence the proper development and survival of parasitic plant populations 18 , 74 , 75 . Also, different parasite-host pairs vary in the overlap of ecological tolerances influencing their habitat distribution 29 . Temperature and seed moisture content at the beginning of conditioning play key roles in the seed germination of holoparasitic species (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species Distribution Models (SDMs), also known as Ecological Niche Models (ENMs), have previously been used to predict the potential invasion ranges of pests and the suitability of BCAs 12,24–26 . Climate is a key factor in determining species distribution, especially for ectothermic animals such as insects, so it is regarded as the primary environmental variable in SDM studies 27–31 . The MaxEnt species distribution modeling technique has the advantage of requiring only species occurrence records and environmental variables, making it one of the most commonly used models 32–36 …”
Section: Introductionmentioning
confidence: 99%
“…12,[24][25][26] Climate is a key factor in determining species distribution, especially for ectothermic animals such as insects, so it is regarded as the primary environmental variable in SDM studies. [27][28][29][30][31] The MaxEnt species distribution modeling technique has the advantage of requiring only species occurrence records and environmental variables, making it one of the most commonly used models. [32][33][34][35][36] The application of host plant geographical distribution records to current and future climate conditions is potentially an effective way to improve simulations of host-pest distribution.…”
Section: Introductionmentioning
confidence: 99%